2019
DOI: 10.1021/acs.jpcc.8b12392
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of Redox Conductivity and Electrocatalytic Activity in Metal–Organic Framework Films Via Control of Defect Site Density

Abstract: Redox-active Metal−Organic Frameworks (MOFs) are considered as promising platforms for assembling high quantities of solutionaccessible molecular catalysts on conductive surfaces, toward their utilization in electrochemical solar fuel related reactions. Nevertheless, slow redox hopping-based conductivity often constitutes a kinetic bottleneck hindering the overall electrocatalytic performance of these systems. In this work, we show that, by a systematic control of MOF defect site density, one can modulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 68 publications
0
59
0
Order By: Relevance
“…Therefore, these defective sites incorporating conductive guests can increase the charge transfer rate by an order of magnitude. See Figure 12A (Shimoni et al, 2019). Another strategy to improve the electrocatalysis properties is to synthesize MOF-derived NPC nanomaterials.…”
Section: Emerging Contaminantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these defective sites incorporating conductive guests can increase the charge transfer rate by an order of magnitude. See Figure 12A (Shimoni et al, 2019). Another strategy to improve the electrocatalysis properties is to synthesize MOF-derived NPC nanomaterials.…”
Section: Emerging Contaminantsmentioning
confidence: 99%
“…The NPC exhibits a comparable ORR activity, higher stability, and better tolerance to methanol compared with the commercial Pt/C. The density functional theory results show that N-doped carbon along with the defects is more favorable for ORR compared with N-doped carbon because the presence of FIGURE 12 | (A) Fe-porphyrin-based (Hemin)-modified UiO-66 (UiO-66@Hemin) made by defective UiO-66 (Shimoni et al, 2019). (B) Schematic diagram of the synthesis of the pore size-enlarged NPC nanomaterials derived from ZIF-8 precursors (Zhu et al, 2019).…”
Section: Emerging Contaminantsmentioning
confidence: 99%
“…In 2017, this team further reported their investigation of Ni 3 (HITP) 2 as electrode material for electrochemical capacitors (ECs) for the first time and found that this kind of material had superior capacitive behavior 16 . The contribution inspires the worldwide research interests in extensive exploration of conductive MOFs for electrochemical energy‐related applications such as ECs, 17 secondary batteries, 18 high power density and energy density ion capacitors, 19 electrocatalysis, 20 and so on, as manifested in Figure 1B.…”
Section: Introductionmentioning
confidence: 98%
“…As an outcome of these mentioned virtues, over the passed two decades, MOFs have attracted great attention from the scientific community due to the scope of using either pristine MOFs or MOFderived materials in various important applications. They have also been extensively evaluated as highly promising candidate materials for the design of efficient renewable energy based electrochemical devices e.g., supercapacitors, batteries, and electrocatalysis [5,17,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%